Antagonista do receptor tipo AMPA reverte a modulação pré-frontal induzida pela estimulação epidural por corrente contínua na memória operacional espacial - Martins, Cleciane Waldetário (2016)
The modulation of the prefrontal cortex (PFC) excitability by direct current stimulation improves cognitive function. However, the underlying mechanisms remains unknown. Here we investigated the involvement of glutamate α-amino-3-hydroxy-5-methyl-4- isoxazole propionic acidreceptors (AMPARs) on the effects of repetitive epidural direct current stimulation (eDCS) on long-termed spatial working memory. Methods: Well-trained rats in 8-arm radial maze (8-RM) procedures received acute intraperitoneal (IP) administration of the AMPAR antagonist, perampanel (PRP, 1 mg/kg) or its vehicle (VEH) before performing 4-h delayed tasks in 8-RM. This drug intervention was performed before or after repetitive (once daily, five consecutive days) anodal eDCS (400 µA, 13 minutes) over the left medial PFC or sham procedure. Results: Animals treated with PRP (n = 27) showed larger number of errors (p < 0.01) in the 4-h post-delayed performance compared to those treated with VEH (n = 26). After the repetitive eDCS, animals treated with VEH (n = 13) presented smaller number of errors in the 4-h post-delay performance compared to animals receiving VEH after sham (p = 0.05, n = 12) and those receiving PRP after eDCS (p= 0.001, n = 13). These animals receiving PRP after eDCS showed larger (p = 0.025) number of errors when compared to those treated with PRP after sham (n = 12). Conclusions: AMPARs antagonism disrupted the spatial working memory and reversed the facilitating effects of the eDCS applied over the medial PFC. Thus, the spatial working memory and the prefrontal cognitive modulation by the direct current stimulation are highly dependent on AMPARs activity.